Local electrical potential detection of DNA by nanowire–nanopore sensors - Lieber, Charles M. (2013)
Nanopores could potentially be used to perform single-molecule DNA sequencing at low cost and with high throughput1, 2, 3, 4. Although single base resolution and differentiation have been demonstrated with nanopores using ionic current measurements5, 6, 7, direct sequencing has not been achieved because of the difficulties in recording very small (~pA) ionic currents at a bandwidth consistent with fast translocation speeds1, 2, 3. Here, we show that solid-state nanopores can be combined with silicon nanowire field-effect transistors to create sensors in which detection is localized and self-aligned at the nanopore. Well-defined field-effect transistor signals associated with DNA translocation are recorded when an ionic strength gradient is imposed across the nanopores. Measurements and modelling show that field-effect transistor signals are generated by highly localized changes in the electrical potential during DNA translocation, and that nanowire–nanopore sensors could enable large-scale integration with a high intrinsic bandwidth.